PERANAN CUSTOMER SERVICE DALAM MENINGKATKAN KEPUASAN PELANGGAN - I Wayan Astawa (STIE BIITM, 2018)
In the current era of Globalization, the role of inter-sesame communication is necessary in the business world, in order to establish a good relationship, be it between superiors and subordinates, subordinates with superiors as well as between employees with customers or costomers, especially in the modern times. Bali is famous for its well-known culture and tourism all over the world. Along with the development of business in Bali, the role of the virtual world that the Internet is very supportive of these developments. The internet is very telling without looking geographically. Business connection or internet service is growing rapidly. Price competition, service, and supprortpun increasingly tight. In Bali unlike a few years ago, it is currently reatif easy to get internet access. Starting from the bandwidth / data transfer of the smallest to the unlimited, ranging from the Wireleess / wifi, mobile phone network, and using telephone line. Even now there are many places to eat / restaurants, malls, and so on, which provides Hot Spot free or paid internet access. The role of Customer Service is the actions performed in providing services to customers and prospects. For that Customer Service must have the ability, patience, reliability, look good and neat, be friendly, and able to communicate well to create a good relationship with customers. All that can be done by showing a high passion and show attitude always ready to provide the best service to the customer.